The Influencing Factors of Two-Flow Rate Well Test in Low-Permeability Reservoirs - ZHANG Lisha; ZOU Pinguo; ZHU Miaomiao; XU Yang; HU Peng; ZHAO Dan (Cejing jishu)
In order to solve the problems of low success rate and large interpretation error of two-flow rate well test in low permeability reservoir, this paper starts from the testing principle and interpretation principle of two-flow rate well test technology in low permeability reservoir. Based on the geological characteristics and production characteristics of low permeability reservoir, the field test, bottom hole pressure conversion and formation parameter calculation are emphatically analyzed, the main problems and influencing factors in two-flow rate well test, bottom hole pressure conversion and formation parameter calculation in low permeability reservoir are analyzed in detail. This paper puts forward the improvement measures and carries out a lot of practices on the spot, the field practice shows that the improved measures can effectively improve the test success rate and interpretation coincidence rate of the two-flow rate well test in low permeability reservoirs, and contribute to the popularization and application of this technology, to provide more reliable data support for oilfield production and measure adjustment.